Approach to ESG Risk Assessment of Construction Companies Considering Financial Data - Ermilova, Mariia; Rebeka, Evgenii; Rodiontsev, Roman (Journal of Ecohumanism, 2024)
In modern conditions, environmental, social and corporate responsibility (ESG) factors are becoming increasingly important in assessing the sustainability and financial performance of companies, especially in resource-intensive industries such as construction. The purpose of this study is to develop and apply a comprehensive methodology for assessing ESG risks of construction companies taking into account financial indicators. Due to the limited availability of ESG data of Russian construction firms, the methodology was tested on hypothetical companies X, Y and Z, which allowed to demonstrate the assessment process and identify the potential of the methodology for practical application. The study collected and normalized data on environmental, social and governance factors, as well as financial indicators, using weighting factors to reflect the relative importance of each indicator. The results showed significant differences between companies, identifying areas for improvement and providing customized recommendations to improve their ESG performance and financial sustainability. The methodology proved to be effective even with limited data availability, offering a valuable tool for companies and investors to assess and improve ESG practices in the construction sector